Autonomous detection and ascent of a step for an electric wheelchair. (October 2022) - Botta, Andrea; Bellincioni, Roberto; Quaglia, Giuseppe
Abstract: With the number of individuals using a wheelchair on the rise, the issue of removing architectural barriers, or at least overcoming them, has to be faced to improve independence, inclusiveness, and participation of wheelchair users. Some electric wheelchairs can climb and descend stairs and obstacles, however, the actual operations required to do so safely may be complex and may require an experienced or trained user. To overcome this issue, a method to first detect and classify a step and then autonomously climb it safely is proposed here. The same method is then applied and tested on an actual stair-climbing wheelchair prototype to prove its reliability in different conditions. Highlights: This paper addresses the problem of architectural barriers and wheelchairs. This study proposes a method to classify a step. This study proposes an autonomous step climbing wheelchair. The proposed solutions were tested on an actual prototype.